MR diffusion tractography - Behrens, T; Jbabdi, S (Elsevier, 2009)
This chapter describes the underlying principles and most common techniques in diffusion tractography and covers deterministic streamline tractography and several different probabilistic approaches. Tractography is the process of integrating voxelwise fiber orientations into a pathway that connects remote brain regions. MR diffusion tractography is a method for identifying white matter pathways in the living human brain. These pathways form the substrate for information transfer between remote brain regions and are therefore central to our understanding of function in both the normal and diseased brain. Tractography is the only available tool for identifying and measuring these pathways non-invasively and in vivo. All diffusion tractography techniques rely on one fundamental assumption: that, when a number of axons align themselves along a common axis, the diffusion of water molecules will be hindered to a greater extent across this axis than along it. The data and modeling upon which tractography relies are subject to errors, and these errors propagate through the tractography process, potentially leading to erroneous statements about white matter connectivity. The goal of probabilistic tractography is, instead of simply stopping tractography in regions and along trajectories in which such errors are likely, to develop a full representation of the uncertainty associated with any eventual statement that might be made. Different tractography techniques are appropriate in different circumstances and for different scientific questions. No matter which tractography technique is used, however, it is important to remember the reliance on diffusion tractography's fundamental assumption: a consistent and known relationship between bulk average diffusion properties measured at a macroscopic scale, and microscopic properties of the local white matter. © 2009 Copyright © 2009 Elsevier Inc. All rights reserved.